2019
DOI: 10.1016/j.jgr.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Gintonin-mediated release of astrocytic vascular endothelial growth factor protects cortical astrocytes from hypoxia-induced cell damages

Abstract: Background Gintonin is a ginseng-derived exogenous ligand of the G protein-coupled lysophosphatidic acid (LPA) receptor. We previously reported that gintonin stimulates gliotransmitter release in primary cortical astrocytes. Astrocytes play key roles in the functions of neurovascular systems. Although vascular endothelial growth factor (VEGF) is known to influence the normal growth and maintenance of cranial blood vessels and the nervous system, there is little information about the effect of gint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The authors indicated that gintonin markedly regulated amyloid-β-induced cholinergic impairment, e.g., through reduced acetylcholine level and diminished ChAT activity, and increased the level of AChE [ 28 ]. Moreover, it was shown that gintonin regulates the expression of VEGF in astrocytes, which might provide protection against hypoxic injury [ 76 ]. It has been suggested that gintonin is able to protect mouse brain against methylmercury-induced neurotoxicity and learning processes [ 77 ].…”
Section: Effects Of Gintonin Against Different Models Of Neurodegmentioning
confidence: 99%
“…The authors indicated that gintonin markedly regulated amyloid-β-induced cholinergic impairment, e.g., through reduced acetylcholine level and diminished ChAT activity, and increased the level of AChE [ 28 ]. Moreover, it was shown that gintonin regulates the expression of VEGF in astrocytes, which might provide protection against hypoxic injury [ 76 ]. It has been suggested that gintonin is able to protect mouse brain against methylmercury-induced neurotoxicity and learning processes [ 77 ].…”
Section: Effects Of Gintonin Against Different Models Of Neurodegmentioning
confidence: 99%
“…5 A, coadministration of Ki16425 with gintonin + DPZ abolished gintonin-mediated enhancement of brain delivery of DPZ, indicating that gintonin-mediated enhancement of brain delivery of DPZ is achieved via LPA1/3 receptors. In previous reports, we showed that gintonin stimulates VEGF release in human umbilical vessel endothelial cells and astrocytes [ 16 , 17 ]. Furthermore, it was reported that VEGF is a kind of BBB opening agent [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“… 3 We further showed that in vitro gintonin-mediated cellular effects via LPA receptors are coupled to beneficial effects in animal models of neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD). 8 , 10 , 17 , 18 Although previous in vitro and in vivo studies demonstrated GEF-mediated actions on normal brain and neurodegenerative diseases after oral administration, the effects of GEF on a broad spectrum of genetic expressions in animal brain, especially in the hippocampus was not fully understood. In the present study, we used NGS analysis (RNA-seq) to elucidate GEF-mediated gene expression regulations.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In in vivo studies, gintonin-mediated activation of LPA-LPA receptor axis induces many beneficial brain functions; the increased hippocampal synaptic transmission and long-term potentiation (LTP), brain-derived neurotrophic factor (BDNF) expression, attenuation of hippocampal aging, enhancement of hippocampal dependent-cognitive functions, and finally prevention and attenuation of neurodegenerative diseases. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%